Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

Can TK-TD modelling bridge the gap between in vitro and in vivo mammalian toxicity data? - Thomas Martin; Mark E. Hodson; Helen Thompson; Victoria Hutter; Roman Ashauer (Toxicology in Vitro, 2024)

Profiling alveolar macrophage responses to inhaled compounds using in vitro high content image analysis - Ewelina Hoffman; Laura Urbano; Abigail Martin; Rhamiya Mahendran; Aateka Patel; Darragh Murnane; Clive Page; Lea Ann Dailey; Ben Forbes; Victoria Hutter (Toxicology and Applied Pharmacology, 2023)

Morphometric Characterization of Rat and Human Alveolar Macrophage Cell Models and their Response to Amiodarone using High Content Image Analysis - Ewelina Hoffman; Aateka Patel; Doug Ball; Jan Klapwijk; Val Millar; Abhinav Kumar; Abigail Martin; Rhamiya Mahendran; Lea Ann Dailey; Ben Forbes; Victoria Hutter (Pharmaceutical Research, 2017)